THE STUDY OF THAI DIGITAL TYPOGRAPHY - Jitpimolmard, Siriya (PEOPLE: International Journal of Social Sciences, 2018)
Although it is highly disputed among typographers that the existence of public domain is considered a disadvantage for graphic designers to pursue basic skills to generate work (Cole, 2005: Austin, 2002; Supanun, 2015). Moreover, it is also disconnecting the culture and history reflecting within the Thai typography design itself (Supanun, 2015). Nonetheless, this paper is proposing www.f0nt.com/ (2018), the first typographic public domain website (Iannnnn, 2007), as case study of the most important achieve for Thai digital contemporary typographic history, development and progress.The research analyzed and classified all typefaces available on the website using method of Wilks and Wyse (2017) with additional context of Thai typography design and usage. The result shows 430 existing typefaces being designed during the past 14 years (2004-2018) with 134,249,910 downloads in total. The highest produced font is script font with 222 fonts available, following by ornamented/novelty and display with 63 and 53 fonts, respectively. The research result shows the development with basic design application being zero at the starting of the website in 2004 has increased to 100 percent in present year. Which has proven that the public domain is not always the disadvantage for producing quality graphics work.